Cardiovascular Risk Assessment Using Ultrasonographic Surrogate Markers of Atherosclerosis and Arterial Stiffness in Patients With Chronic Renal Impairment: A Narrative Review of the Evidence and a Critical View of Their Utility in Clinical Practice - Kousios, Andreas (Can J Kidney Health Dis, 2020)
PURPOSE OF THE REVIEW: Validated tools to improve cardiovascular disease (CVD) risk assessment and mortality in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) are lacking. Noninvasive measures of arteriosclerosis and subclinical atherosclerosis such as pulse wave velocity (PWV) and carotid intima-media thickness (cIMT), respectively, have emerged as promising risk stratification tools and potential modifiable biomarkers. Their wide use as surrogate markers in clinical research studies is based on the strong pathophysiological links with CVD. However, whether their effect as risk stratification or intervention targets is superior to established clinical approaches is uncertain. In this review, we examine the evidence on the utility of PWV, cIMT, and plaque assessment in routine practice and highlight unanswered questions from the clinician’s perspective. SOURCES OF INFORMATION: Electronic databases PubMed and Google Scholar were searched until February 2020. METHODS: This narrative review is based on peer-reviewed meta-analyses, national and international societies’ guidelines, and on focused critical review of recent original studies and landmark studies in the field. KEY FINDINGS: Although patients with CKD are considered in the high-risk CVD groups, there is still need for tools to improve risk stratification and individualized management strategies within this group of patients. Carotid intima-media thickness is associated with all-cause mortality, CVD mortality, and events in CKD and hemodialysis cohorts. However, the evidence that measurement of cIMT has a clinically meaningful role over and above existing risk scores and management strategies is limited. Plaque assessment is a better predictor than cIMT in non-CKD populations and it has been incorporated in recent nonrenal-specific guidelines. In the CKD population, one large observational study provided evidence for a potential role of plaque assessment in CKD similar to the non-CKD studies; however, whether it improves prediction and outcomes in CKD is largely understudied. Pulse wave velocity as a marker of arterial stiffness has a strong pathophysiological link with CVD in CKD and numerous observational studies demonstrated associations with increased cardiovascular risk. However, PWV did not improve CVD reclassification of dialysis patients when added to common risk factors in a reanalysis of ESRD cohorts with available PWV data. Therapeutic strategies to regress PWV, independently from blood pressure reduction, have not been studied in well-conducted randomized trials. LIMITATIONS: This study provides a comprehensive review based on extensive literature search and critical appraisal of included studies. Nevertheless, formal systematic literature review and quality assessment were not performed and the possibility of selection bias cannot be excluded. IMPLICATIONS: Larger, prospective, randomized studies with homogeneous approach, designed to answer specific clinical questions and taking into consideration special characteristics of CKD and dialysis, are needed to study the potentially beneficial role of cIMT/plaque assessment and PWV in routine practice.